Prospective assessment of peripheral neuropathy in Duodopa‐treated parkinsonian patients. (9th July 2013) - Merola, A.; Zibetti, M.; Rizzone, M. G.; Troiano, M.; Artusi, C. A.; Angrisano, S.; Cocito, D.; Lopiano, L.
<x xml:space="preserve">Abstract</x> Background Although peripheral neuropathies (PN) have been described in patients with Parkinson's disease (PD) treated with oral dopaminergic therapies, anecdotal reports of subacute severe PN have been reported during treatment with enteral levodopa/carbidopa infusion (Duodopa). Aim of the study We prospectively assessed clinical and electrophysiological data of 15 consecutive patients with PD treated with Duodopa for a mean follow‐up of 9 months. Methods Nerve conduction studies and a clinical evaluation with a standardized battery of peripheral neuropathy scales were performed at baseline and after a mean follow‐up of 9 months. Results At baseline, mild signs of PN were observed in three subjects, and vitamin B12 serum levels were found to correlate with the amplitude of sural sensory action potentials. Follow‐up data were available for 10/15 subjects: one patient developed a subacute sensory‐motor PN and three subjects with pre‐existing PN showed a moderate worsening of electrophysiological and clinical features. Subclinical electrophysiological alterations of peripheral nerves were observed in two subjects. No significant changes were observed in vitamin B12, folate, homocysteine and methylmalonic acid levels. Conclusions In this consecutive series of patients treated with Duodopa, we observed one subacute sensory‐motor PN and few length‐dependent alterations of peripheral nerves, similar to those described during oral levodopa treatment.